PEMBUATAN EDIBLE STRAW DENGAN MEMANFAATKAN WATER RESISTANT SODIUM ALGINATE - Moh. Iwangga Kalih Syah Putra; Azwin Apriandi; Sri Novalina Amrizal (Marinade, 2023)
The current global production of plastic is very high and majority of this plastic waste is not recycled or incinerated, thus creating environmental problems. As an alternative, alginate, a stable polymer, can be used as an environmentally friendly material. The aim of this research is to evaluate the potential of alginate as a plastic replacement through testing of natural degradation, water solubility, and in vitro gastric acid results on edible straw made from it. The most significant result was found in the natural degradation test, which is the higher the concentration of E.cottonii in the edible straw, the more fragile the straw will be produced. The other two tests did not show significant results.